2015
DOI: 10.1186/s12978-015-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Critical maternal health knowledge gaps in low- and middle-income countries for the post-2015 era

Abstract: Effective interventions to promote maternal health and address obstetric complications exist, however 800 women die every day during pregnancy and childbirth from largely preventable causes and more than 90 % of these deaths occur in low and middle income countries (LMIC). In 2014, the Maternal Health Task Force consulted 26 global maternal health researchers to identify persistent and critical knowledge gaps to be filled to reduce maternal morbidity and mortality and improve maternal health. The vision of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 2 publications
1
46
0
Order By: Relevance
“…30 However, these guidelines fail to translate in clinical practice. 31 For example, a study on public hospitals between 2004 and 2006 found that episiotomy is avoided only in 41.2% of primiparous pregnancies and that continuous support of women during childbirth occurs only in 17.9% of cases. 32 An analysis of cesarean rates also points in the same direction.…”
Section: Obstetric Violence As a Public Health Issuementioning
confidence: 99%
“…30 However, these guidelines fail to translate in clinical practice. 31 For example, a study on public hospitals between 2004 and 2006 found that episiotomy is avoided only in 41.2% of primiparous pregnancies and that continuous support of women during childbirth occurs only in 17.9% of cases. 32 An analysis of cesarean rates also points in the same direction.…”
Section: Obstetric Violence As a Public Health Issuementioning
confidence: 99%
“…On the other hand, strong evidence for women with HIV is still missing. The fact that strong evidence linking community mobilization to maternal health outcomes for women with HIV is still missing confirms Kendall and Langer's (2015) assertion that the intersection of HIV and pregnancy has generally been ignored in social science research (Kendall & Langer, 2015). This is despite the fact that women with HIV are more susceptible to morbidity and mortality during pregnancy (Kendall, et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…In resource-poor settings where health systems are inefficient, research has shown that community mobilization can be a useful strategy for improving maternal care of HIV negative women (Colbourn, et al, 2013). Chapter 2 of this dissertation and other studies from SSA have shown that similar evidence for HIV positive women is still lacking despite them being more vulnerable given their HIV status (Kendall & Danel, 2004;Kendall & Langer, 2015). Besides the lack of evidence of the effect of community mobilization on maternal health care service provision for HIV positive women, there is a lack of evidence on local stakeholders' (HIV positive women) own perspectives of community mobilization vis-à-vis maternal health care (Kendall & Danel, 2004;Nhamo, et al, 2010;Lassi, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations